Investigating consumers' brand desirability for upcycled luxury brands. (15th August 2022) - Phau, Ian; Akintimehin, Olamide Oluwabusola; Lee, Sean
Abstract: This paper investigates consumers' values on attitude and brand desirability for upcycled luxury designer shirts. Consumer values in the present study's context consist of terminal and instrumental values. Findings show that terminal values do not strongly influence the attitude towards the Burberry previous collection shirts nor brand desirability for the Burberry leftover fabric shirts and the Burberry previous collection shirts compared to Burberry generic shirts. Instrumental values do not strongly influence the attitude towards the Burberry leftover fabric shirts. Still, a stronger influence on brand desirability for the Burberry previous collection shirts than Burberry generic shirts. Managerial and strategic implications should focus on instrumental values to evoke favorable luxury brand desirability.